Five-level Cascaded Multilevel H-Bridge Inverter for Single-Phase PV Grid-Connected System - Sakdawut Boontua; Prayad Kongsuk; Vijit Kinnares (My University, 2021)
This research presents the applied P&O MPPT control technique for controlling real power and reactive power (PQ) of a single-phase five-level H-bridge multilevel inverter for a PV grid-connected system (FHB-MLI for PVGCS) under weak irradiation condition. Perturb and Observe (P&O) maximum power point tracking (MPPT) technique is used in this system to keep dc-link voltage constant for maximum power to be maintained for each module. The proposed controller regulates the actual dc-link voltage independent of each other under imbalance of power irradiation of each PV and varies real power and reactive power with magnitude and power angle of grid-current. The validation of the proposed method is verified by simulation using MATLAB/SIMULINK program and promising experiment. Simulation results, with a setup consisting of real power and reactive power processing by weak irradiation condition and two PV modules, indicate that the overall system can operate satisfactorily even in conditions with different irradiation of the modules injecting available maximum power to the grid.
Keywords: Multilevel Inverters and Converters; Microgrid Control and Optimization; Advanced DC-DC Converters